Different functional lung-sparing strategies and radiotherapy techniques for patients with esophageal cancer - Zhou, Pi-Xiao; Wang, Rui-Hao; Yu, Hui; Zhang, Ying; Zhang, Guo-Qian; Zhang, Shu-Xu (Frontiers in Oncology, 2022)
Backgrounds: Integration of 4D-CT ventilation function images into esophageal cancer radiation treatment planning to assess dosimetric differences between different functional lung (FL) protection strategies and radiotherapy techniques. Methods: A total of 15 patients with esophageal cancer who had 4D-CT scans were included. Lung ventilation function images based on Jacobian values were obtained by deformation image registration and ventilation imaging algorithm. Several different plans were designed for each patient: clinical treatment planning (Non-sparing planning), the same beams distribution of FL-sparing planning, three fixed-beams FL-sparing IMRT (intensity-modulate radiation therapy) planning (5F-IMRT, 7F-IMRT, 9F-IMRT), and two FL-sparing VMAT (volumetric modulated arc therapy) planning (1F-VMAT (1-Arc), 2F-VMAT (2-Arc)). The dosimetric parameters of the PTV (planning target volume) and organs at risk (OARs) were compared and focused on dosimetric differences in FL. Results: The FL-sparing planning compared with the Non-sparing planning group significantly decreased the FL-Dmean, V5-30 and Lungs-Dmean, V10-30 (Vx: volume of receiving ≥X Gy), although slightly compromised PTV conformability and increased Heart-V40 (P <0.05). 5F-IMRT had the lowest PTV-CI (conformability index), but had a lower Lungs and Heart irradiation dose compared with 7F-IMRT and 9F-IMRT (P <0.05). 2F-VMAT had higher PTV-HI (homogeneity index) and reduced irradiation dose to FL, Lungs, and Heart compared to the 1F-VMAT planning (P <0.05). 2F-VMAT had higher PTV conformability and homogeneity, and decreased FL-Dmean, V5-20 and Lungs-Dmean, V5-10, but correspondingly increased spinal cord-Dmean compared with the 5F-IMRT planning (P <0.05). Conclusion: 4D-CT ventilation function image-based FL-sparing planning for esophageal cancer can effectively reduce the dose of the FL. The 2F-VMAT planning is better than the 5F-IMRT planning in reducing the dose of FL.